The Impact of the Secondary Market on the Supply Chain - Lee, Hau; Whang, Seungjin (Management Science, 2002)
This paper investigates the impacts of a secondary market where resellers can buy and sell excess inventories. We develop a two-period model with a single manufacturer and many resellers. At the beginning of the first period resellers order and receive products from the manufacturer, but at the beginning of the second period, they can trade inventories among themselves in the secondary market. We endogenously derive the optimal decisions for the resellers, along with the equilibrium market price of the secondary market. The secondary market creates two interdependent effect—a quantity effect (sales by the manufacturer) and an allocation effect (supply chain performance). The former is indeterminate; i.e., the total sales volume for the manufacturer may increase or decrease, depending on the critical fractile. The latter is always positive; i.e., the secondary market always improves allocative efficiency. The sum of the effects is also unclear—the welfare of the supply chain may or may not increase as a result of the secondary market. Lastly, we study potential strategies for the manufacturer to increase sales in the presence of the secondary market.